Electrotactile display using microfabricated micro-needle array. (22nd January 2015) - Kitamura, N; Chim, J; Miki, N
Abstract: This paper describes an electrotactile display with micro-needle electrodes. The electrotactile display can produce tactile sensations by stimulating tactile receptors using an electric current. Micro-needle electrodes can drastically decrease the threshold voltage required to stimulate tactile receptors by penetrating the stratum corneum, which has a higher impedance than the dermis. In addition, the optimized length of the needle allows us to stimulate tactile receptors painlessly. In the present study, we developed a process for fabricating a micro-needle array in which the length and tip radius can be controlled using electrochemical etching. A micro-needle array was successfully fabricated to form an electrotactile display. In addition, we experimentally determined the suitable shape of the micro-needle electrodes for electrotactile display applications. When the tip radius of the needle is too small, the impedance between the finger and micro-needles becomes large due to the small contact area. On the other hand, when the tip radius is too large, the needle cannot penetrate the skin surface and the impedance is not sufficiently small. The experiments verified the superiority of needle electrode devices to flat electrode devices with respect to the threshold voltage at each frequency.